Language Features Used by Main Female Character in the Movie Redeeming Love (2022) - Amar, Rizki Oktavianti; Wulandari, Dwi (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2024)
The research an titled "Language Features Used by Main Female Character in the Movie Redeeming Love (2022) focuses on identifying and describing specific women’s language features utilized by Angel as the main female character in the movie Redeeming Love. The research also aims to examine the functions of these language features employed Angel with theories of Coates and Holmes were used for these purposes. This descriptive qualitative research utilized purposive sampling to collect data from the Redeeming Love (2022) movie and Redeeming Love movie script. Then, the data were examined by determining and classifying the types of women's language defined by Coates and supported by using Holmes’s theory as a social factor that influences language. The results of the analysis revealed that the main female characters uses all variety of women's language features, including minimal responses, lexical hedges, tag questions, questions, commands and directives, swearing and taboo language, and compliments. Additionally, Angel utterances are mainly used for expressive functions among other. The study also shows social factor that Angel mostly used is participant.